Innovative learning methods during seminar classes at higher educational institutions - Bukhkalo, Svіtlana Ivanovna; Ageicheva, Anna Oleksandrivna; Rozhenko, Inesa Vitaliivna; Shkil, Svitlana Oleksandrivna (Національний технічний університет "Харківський політехнічний інститут", 2023)
The importance of teaching students a foreign language by innovating study methods is investigated. It is being set that it is necessary to strengthen the communicative component when teaching a foreign language as a foreign language. The usage of cases in classes are investigated. It is studied that classic case promotes the development of independent decision-making skills, the second purpose of working with the case in the classroom is a communicative practice. It is described possible cases and presents the development of the proposed concept in the article. Case study technology for the formation of critical thinking skills is described in the article. It was determined that the systematic use of the case study method in the study of the English language makes it possible to effectively form critical thinking skills. The use of various methods and techniques of active learning arouses students' interest in the educational and cognitive activity itself, which enables creating an atmosphere of motivated, creative learning and at the same time solving a whole range of educational, educational, developmental tasks.

У статті обґрунтовується важливість навчання студентів іноземної мови інноваційними методиками. Встановлено, що при навчанні іноземної мови як іноземної необхідно посилювати комунікативну складову. Досліджено використання кейсів на заняттях. Вивчено, що класичний кейс сприяє розвитку навичок самостійного прийняття рішень, другою метою роботи з кейсом на занятті є комунікативна практика. У статті описано можливі випадки та представлено розвиток запропонованої концепції. У статті описано технологію кейс-стаді для формування навичок критичного мислення. Встановлено, що системне використання методу кейс-стаді при вивченні англійської мови дає змогу ефективно формувати навички критичного мислення.
Інноваційні методи навчання під час семінарських занять у закладах вищої освіти
Keywords: case studies; foreign language; communication; innovative teaching methods; кейси; іноземна мова; комунікація; інноваційні методи навчання